Pengaruh Shopping Lifestyle, Discount, Dan Fashion Involment Terhadap Impulse Buying Pada Pelanggan Toko Fashion Malang - Arini Maulidiyah; Nur Hidayati; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine whether there is influence between shopping lifestyle, discounts, and fashion involvement on impulse buying at Toko Fashion Malang customers. The type of research used in this study is a quantitative descriptive research. The data processed in this study is the result of distributing questionnaires to customers who have visited and made purchases at the fashion Malang store, totaling 110 respondents. The sampling method is non-probability sampling and the technique used in collecting respondents is snowball sampling. The analysis technique used in this study is multiple linear regression. The results showed that the results of the t test (partial) on shopping lifestyle had an effect on impulse buying indicated by a t value of 4.801, discounts had an effect on impulse buying indicated by a t value of 2.567, and fashion involvement had an effect on impulse buying indicated by a t value of 2.761 while the results of the F test study showed that the F count was 0.000 less than 0.05. This means that shopping lifestyle, discount and fashion involvement simultaneously influence impulse buying at the fashion Malang store. Based on the calculation of the coefficient of determination, it shows that the Adjusted R Square is 69,8% and the remaining 30,2% can be explained by other variables that are not in this study. Keywords : Shopping Lifestyle, Discount, Fashion Involvement and Impulse Buying.